Investigations of embroidery antennas on polymer substrate - Ngo Quang Bao, Loc (2016)
For everyday human life, people desire to stay connected via an advanced wireless network. Although cellular phone is worthy in various applications, people are likely to carry a wide range of mobile devices and constantly connect with each other. Future communication network requires a new class of front-ends electronic devices that are small, light-weight, conformal, multi-functional but also environment-friendly, inexpensive and good performance. In different aspects, once of the key factors to achieve this goal is to integrate the wireless antenna into garments as daily clothes and enhance its durability. Consequently, these wearable antennas need not only possess good RF performance characteristics but also mechanical structure which adaptable to conformity and durability. This dissertation presents a novel class embroidery patch antenna on polymer composite — polydimethylsiloxane (PDMS). By lamination and polymer integration, different structures and feeding techniques of fully embroidered polymer patch antenna with ground plane have been designed, fabricated and tested. Analysis of the effect of conductive patch weight as well as conductive characteristics using different embroidery structures on antenna performance has been carried out. The measured results show that although double embroidered layer on one side of fabric has similar conductivity and identical embroidery properties as two-sided embroidery, the antenna performs better using two-sided embroidery structure in term of reflection coefficient and gain measurement. In respect of conductivity of embroidered layers, the thesis investigates a method to improve the conductivity of embroidered patches used in antennas on polymer composite. Nanopowders which include graphene, zinc oxide (ZnO), aluminum oxide (Al2O3) and copper oxide (CuO) were dispersed in ethanol solvent to prepare as dyeing solutions. The effect of nanopowders on patches resistance has been studied. The measured results show that the patch conductivity improves 11.87% after 7 times dyeing with CuO and 8.14% after 10 times dyeing with ZnO. In contrast, graphene raises up the sheet resistance. The CuO and ZnO dyed conductive patch layers have been laminated and integrated on polymer substrate with embroidered ground plane to analyze the dyeing effect on antenna performance. Although dyeing effect reduces the resonant frequencies, the measured result indicates that dyed patch antennas perform better in term of reflection coefficient level.